Myocardial Injury After Temporary Transvenous Cardiac Pacing - Liu M; Wu P (Dove Medical Press, 2021)
Meng Liu,1,2 Pingsheng Wu2 1Emergency Department, Hunan Provincial People’s Hospital, Medical School of Hunan Normal University, Changsha, People’s Republic of China; 2Cardiology Department, Nanfang Hospital, Southern Medical University, Guangzhou, People’s Republic of ChinaCorrespondence: Pingsheng WuCardiology Department, Nanfang Hospital, Southern Medical University, No. 1838, North Guangzhou Road, Guangzhou, People’s Republic of ChinaTel +86 02061641502Email wupingshengnf@sina.comIntroduction: Temporary transvenous cardiac pacing (TTCP) can lead to potential penetration and occasional perforation of the right ventricular wall. No study to date has analyzed the effect of TTCP on myocardial injury by cardiac troponin (cTn) measurement. The present study was designed to investigate perioperative myocardial injury in elective TTCP in noncardiac surgical settings.Patients and Methods: This retrospective study investigated the data collected from August 2018 through March 2020 from 22 eligible patients who underwent elective TTCP for noncardiac procedures. The patients had a median age of 66 (50– 83) years; six (27.3%) of them were women, and all of them had a baseline cTn < 1 upper reference limit (URL). Cardiac biomarker assays were performed before and after TTCP, and their results were compared.Results: After TTCP, cTn > 1 URL was detected in 20 (91%, N=22) patients. Among these 22 patients, paired t-test comparing assay results before and after TTCP lead insertion showed a mean cTn elevation of 3.599 URL (95% CI: 1.566 to 5.632, P< 0.01), and a mean creatine kinase-MB isoform elevation of 0.1550 URL (95% CI: − 0.01239 to 0.3224, P> 0.05).Conclusion: The study demonstrates a high incidence of myocardial injury associated with TTCP, which should be a matter of concern for the involved physicians.Keywords: temporary pacemaker, temporary transvenous cardiac pacing, myocardial injury, bradycardia, perioperative myocardial injury